Predictive modeling of lower extremity injury risk in male elite youth soccer players using least absolute shrinkage and selection operator regression - Kolodziej, M.; Groll, A.; Nolte, K.; Willwacher, S.; Alt, T.; Schmidt, M.; Jaitner, T. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Purpose To (1) identify neuromuscular and biomechanical injury risk factors in elite youth soccer players and (2) assess the predictive ability of a machine learning approach.